A comparison of the metabolic complications and hospital course of severe anorexia nervosa by binge-purge and restricting subtypes. Issue 4 (8th August 2017) - Rylander, Melanie; Brinton, John T.; Sabel, Allison L.; Mehler, Philip S.; Gaudiani, Jennifer L.
ABSTRACT: This study examines adult patients with severe, life-threatening anorexia nervosa who were admitted to an inpatient, medical stabilization unit between October 1, 2008 and December 31, 2014. Specifically, the study compares anorexia nervosa, binge purge subtype (AN-BP) and anorexia nervosa, restricting subtype (AN-R) on admission measures, hospital course, and outcomes. Of the 232 patients, 46% ( N = 108) had AN-BP. Patients with AN-R manifested a higher frequency of underweight-mediated medical complications, including bone marrow dysfunction, hepatic dysfunction, and hypoglycemia. Understanding the pathophysiologic differences between severe AN-R and AN-BP is essential to understanding the abnormalities seen on clinical presentation, guiding appropriate clinical treatment, and predicting medical complications during refeeding.